Flow estimation of stream networks in Iligan city using geographic information system (GIS) - Tahud, Anacita P.; Estoperez, Noel R. (2015)
In a nationwide effort to provide long-term solution to Mindanao's power crisis, there is a call for additional sources of energy. In order not to increase the country's carbon footprints in effect, additional sources of energy in renewable forms are the most viable option. With Mindanao's estimated hydropower potential of over 1000 MW, identifying potential hydropower sites is the primary step towards harnessing these undeveloped potentials. However, in situ streamflow measurements for this purpose are costly, time-consuming, risky, and impractical when employed at a large scale. An alternative method of flow estimation is employed in this study using remotely-sense data and Geographic Information System (GIS) technology. Auto-delineation of watersheds and stream networks in Iligan are carried out with the use of a 10-m resolution synthetic aperture radar - derived digital elevation model, precipitation, landuse, hydrologic soils, and other datasets. GIS-based simulation and models provide a fast, scalable, practical, risk-free, and efficient estimation of flow at any portion of the stream networks. Information derived from this study is useful to ploicy makers and concerned agencies involved in hydro resource management, planning and development.
Keywords: Hydropower development; Geographic information sytems